Validation of Define Stages in the Development Process of STEM-Based E-Modules with Plant Themes in Children Aged 5-6 Years - Cupfianis Cupfianis; Abna Hidayati (Postgraduate School, Universitas Negeri Padang, 2022)
The background of this research is because the world of education is currently growing, and various kinds of reforms are being carried out to improve the quality and quantity of education. To improve the quality of education, various breakthroughs are needed in curriculum development, learning innovation, and educational infrastructure. Through the Development of (Science, Technology, Engineering, And Mathematics) STEMBased E-Modules, the theme of plants is very attractively designed and packaged in learning multimedia so that it can be taken anywhere and can be accessed anywhere. The E-Modules can be taken anywhere and anywhere. One suitable device is Android. This research uses Research and development (R&D) with a development model (4-D) which consists of 4 stages, namely, Define, Design, Develop and Disseminate. This development model was chosen because this model has a systematic procedure, which is used to develop learning tools, especially learning media in the form of E-Modules. Based on the results of the feasibility validation test from the material, language, and media aspects using a validated questionnaire. The results showed that the plant-themed STEM-based e-modules were very valid with an average score of 89.33% with a content feasibility test percentage of 96%, language feasibility of 92%, and the feasibility of media construction is 80%. So it can be concluded that the process validation of the different stages in the STEM-based E-Module with the theme of Plants with valid criteria.